Mapping the Research of Ferroptosis in Parkinson’s Disease from 2013 to 2023: A Scientometric Review - Chen Y; Wu Z; Li S; Chen Q; Wang L; Qi X; Tian C; Yang M (Dove Medical Press, 2024)
Yingfan Chen,1,2,* Zhenhui Wu,3,* Shaodan Li,2 Qi Chen,2 Liang Wang,2 Xiaorong Qi,1 Chujiao Tian,1 Minghui Yang2 1Medical School of Chinese People's Liberation Army, Beijing, People's Republic of China; 2Department of Traditional Chinese Medicine, the Six Medical Center of Chinese People's Liberation Army General Hospital, Beijing, People's Republic of China; 3College of Pharmacy, Jiangxi University of Chinese Medicine, Nanchang, People's Republic of China*These authors contributed equally to this workCorrespondence: Minghui Yang, Department of Traditional Chinese Medicine, the Six Medical Center, Chinese People's Liberation Army General Hospital, 6 Fucheng Road, Beijing, 100048, People's Republic of China, Tel +86-10-66939651, Email ymh9651@sina.comMethods: Related studies on PD and ferroptosis were searched in Web of Science Core Collection (WOSCC) from inception to 2023. VOSviewer, CiteSpace, RStudio, and Scimago Graphica were employed as bibliometric analysis tools to generate network maps about the collaborations between authors, countries, and institutions and to visualize the co-occurrence and trends of co-cited references and keywords.Results: A total of 160 original articles and reviews related to PD and ferroptosis were retrieved, produced by from 958 authors from 162 institutions. Devos David was the most prolific author, with 9 articles. China and the University of Melbourne had leading positions in publication volume with 84 and 12 publications, respectively. Current hot topics focus on excavating potential new targets for treating PD based on ferroptosis by gaining insight into specific molecular mechanisms, including iron metabolism disorders, lipid peroxidation, and imbalanced antioxidant regulation. Clinical studies aimed at treating PD by targeting ferroptosis remain in their preliminary stages.Conclusion: A continued increase was shown in the literature within the related field over the past decade. The current study suggested active collaborations among authors, countries, and institutions. Research into the pathogenesis and treatment of PD based on ferroptosis has remained a prominent topic in the field in recent years, indicating that ferroptosis-targeted therapy is a potential approach to halting the progression of PD.Keywords: Parkinson's disease, ferroptosis, bibliometric analysis, iron accumulation, alpha-synuclein, mitochondrial dysfunction, oxidative stress, lipid peroxidation